Hubungan Pengetahuan Orang Tua Tentang Fluor Dengan Kejadian Karies Gigi Pada Siswa/I Kelas IV-VI Di Sekolah Dasar Negeri Pasir Haur, Kabupaten Bandung Barat - Nurkamila, Mia; Ningrum, Nining; Heriyanto, Yonan; Widyastuti, Tri (Poltekkes Kemenkes Bandung, 2024)
ABSTRACT Elementary school children in grades IV-VI are one of the vulnerable groups in the occurrence of dental caries. One of the causes of dental caries in elementary school children is parents' ignorance about dental caries or its prevention. One of the efforts that need to be made to prevent dental caries is to use fluorine which has two ways of using it, including systemically and locally. The purpose of this study was to determine the relationship between parental knowledge about fluoride and the incidence of dental caries in students in grades IV-VI at Pasir Haur State Elementary School, West Bandung Regency. The research method used was observational analytic with a sample of 113 people taken using total sampling. The analysis used was univariate and chi-square. The results showed that most parents' knowledge had a moderate knowledge category as many as 42 people (37.2%) and the incidence of dental caries in students in grades IV-VI as many as 83 people (73.5%). The test results showed (p-value=0.669> 0.05). It can be concluded that there is no relationship between parental knowledge about fluoride and the incidence of dental caries in students in grades IV-VI at Pasir Haur State Elementary School, West Bandung Regency.